The Role of Social Media in the Intercultural Adaptation of Pekanbaru Immigrants - Tessa Shasrini; Yudi Daherman (UIR Press, 2021)
The role of Social Media in the process of cultural adaptation plays a very important role. Immigrants to foreign cultures have applied various technologies to assist them in cultural adaptation and acculturation processes. In recent years, the most common technique and useful that newcomers use is social media, which plays a role important in connecting people around the world together to share and exchange knowledge and cultural traditions. This research aims to find out the role of Social Media on the intercultural adaptation of Pekanbaru immigrants. By using the method qualitative descriptive through interviews with immigrants at the Pekanbaru Rudenim. Results from this study is that in the adaptation process carried out by immigrants going through several phases, honeymoon phases, culture shock, resolution and integration. Social media It has been used among migrants to maintain contact with family members and friends in their home country